Pauvreté: récits - Roussel, Stéphanie (Triptyque, 2021)
Ce livre est l'histoire de douze textes survivants, rescapés, qui, faute de ressources, auraient pu ne jamais voir le jour. Traversés par le thème de la pauvreté, ces récits troublent le rapport à la famille, à l'éducation, au corps, à la mode, à la nourriture, à la mémoire, à la dette ; les voix, éloquentes et poignantes, s'y font écho autant qu'elles adressent les silences qui persistent.
La nouvelle "Cuisine" de Marilou Craft a été donné à lire au cours LIT3495.
Keywords: approches et analyses; arts; cours; discipline; histoire et politique; intersectionnalité; inégalités; lit3495; pauvreté; point de vue situé; premier cycle; systèmes d'oppressions; thématiques; écriture des femmes*; études littéraires

Decoding Black Women: Policing Practices and Rape Prosecution on the Streets of Philadelphia - Irving, Toni (NWSA Journal, 2008)
Black women are generally displaced as victims of rape. The police response to the sexual assault of black women in general and lower-class black women in particular is illustrative of how sexual ideologies help construct complex social hierarchies that in turn structure rights. How the law currently deals with rape places black women outside of the narrative frames that legitimate entitlement. Rape continues to stand in for, and effectively obscure, other social, political, and economic concerns. Unpublished and often ignored, the rape narrative is a ripe site to supply oppositional interpretations of national experience and transmit some of the structural problems in the criminal justice system. Pulling from over two thousand “real” rape cases of low-income black women ignored and not investigated in Philadelphia between 1995 and 2000, this article reads black female rape narratives as case studies in order to discuss the way personal narratives of rape victims are structured by competing and overwhelming sociolegal narratives that undercut their reception. As the fastest growing prison population, the presence of the law to punish black women stands in stark contrast to the absence of the law to protect them.
Keywords: 1900-1999; 1990-1999; afro-féminisme; amériques; approches et analyses; arts; corps; cours; discipline; droit; droit des femmes* noires; droits des femmes*; féminisme afroaméricain; histoire et politique; intersectionnalité; inégalités; philadelphie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sex2283; sexisme; systèmes d'oppressions; thématiques; viol; violences; états-unis; études littéraires

Dangerous liaisons: gender, nation and postcolonial perspectives - McClintock, Anne; Shohat, Ella; Mufti, Aamir Rashid (Minnesota University Press, 1997)
This collection addresses the issues raised by the postcolonial condition, considering nationhood, history, gender and identity from an interdisciplinary perspective.
Contenu: Introduction / Aamir Mufti and Ella Shohat – pt. I. Contesting Nations. 1. Zionism from the Standpoint of Its Victims / Edward W. Said. 2. Sephardim in Israel: Zionism from the Standpoint of Its Jewish Victims / Ella Shohat. 3. Of Balkans and Bantustans: Ethnic Cleansing and the Crisis in National Legitimation / Rob Nixon. 4. "No Longer in a Future Heaven": Gender, Race, and Nationalism / Anne McClintock. 5. Currying Favor: The Politics of British Educational and Cultural Policy in India, 1813-54 / Gauri Viswanathan. 6. The Nation as Imagined Community / Jean Franco – pt. II. Multiculturalism and Diasporic Identities. 7. On the Question of a Theory of (Third) World Literature / Madhava Prasad. 8. Caliban Speaks Five Hundred Years Later / Roberto Fernandez Retamar. 9. The Local and the Global: Globalization and Ethnicity / Stuart Hall. 10. Multiculturalism and the Neoconservatives / Robert Stam. 11. Shuckin' Off the African-American Native Other: What's "Po-Mo" Got to Do with It? / Wahneema Lubiano. 12. Identity, Meaning, and the African-American / Michael Hanchard. 13. Just Looking for Trouble: Robert Mapplethorpe and Fantasies of Race / Kobena Mercer – pt. III. Gender and the Politics of Race. 14. Under Western Eyes: Feminist Scholarship and Colonial Discourses / Chandra Talpade Mohanty. 15. Traddutora, Traditora: A Paradigmatic Figure of Chicana Feminism / Norma Alarcon. 16. American Indian Women: At the Center of Indigenous Resistance in Contemporary North America / M. Annette Jaimes and Theresa Halsey. 17. "On the Threshold of Woman's Era": Lynching, Empire, and Sexuality in Black Feminist Theory / Hazel V. Carby. 18. Making Empire Respectable: The Politics of Race and Sexual Morality in Twentieth-Century Colonial Cultures / Ann Laura Stoler. 19. Age, Race, Class, and Sex: Women Redefining Difference / Audre Lorde. 20. Gender Is Burning: Questions of Appropriation and Subversion / Judith Butler. 21. Sisterhood: Political Solidarity between Women / Bell Hooks – pt. IV. Postcolonial Theory. 22. Not You/Like You: Postcolonial Women and the Interlocking Questions of Identity and Difference / Trinh T. Minh-ha. 23. Is the "Post-" in "Postcolonial" the "Post-" in "Postmodern"? / Kwame Anthony Appiah. 24. The World and the Home / Homi K. Bhabha. 25. Reading Africa through Foucault: V.Y. Mudimbe's Reaffirmation of the Subject / Manthia Diawara. 26. Teaching for the Times / Gayatri Chakravorty Spivak. 27. Postcolonial Criticism and Indian Historiography / Gyan Prakash. 28. The Postcolonial Aura: Third World Criticism in the Age of Global Capitalism / Arif Dirlik. Le texte "Age, Race, Class, and Sex : Women Redefining Difference" de Audre Lorde a été donné en lecture au cours LIT4700.
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; discours dominant; féminisme décolonial; histoire et politique; identités LGBTQIA2+; intersectionnalité; inégalités; lit4700; militance; poésie; premier cycle; queer; racisme; sexisme; systèmes d'oppressions; thématiques; études culturelles; études littéraires